MODEL OF STRUCTURING SETTLEMENT ON THE WA-TER IN COASTAL AREA OF TERNATE - Naidah Naing (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Ternate in North Maluku province has assets with a coastal marine area 5547.55 km2, wider plains than just covering 250.85 km2. Coastal areas become large enough portion for housing development; although prone to disasters, grow uncontrollably, lack of public facilities and the lack of environmental controls. This causes the quality of the coastal environment so declined. Arrangement is needed to prevent the development of sporadic and slums, as well as to anticipate disaster. The purpose of this study is to produce a model of the arrangement of settlements in the coastal zone of the water Ternate, for disaster mitigation. The research method is qualitative with purposive sampling system. The results showed that very precise grid pattern applied in the coastal areas because it can maximize the land use, circulation becomes more fluent evacuation, distribution function and development of the area easier, either macro or micro in accordance with the needs of the region. In addition, the grid pattern can support human circulation and transportation effectively and efficiently.